The discursive construction of superintendent statesmanship on Twitter - Hurst, Todd M. (Education Policy Analysis Archives, 2017)
The modern school superintendent fulfills a unique role in the U.S. public education system. He or she is structurally empowered as the de facto head of the local educational system, thereby granted with a certain amount of trust and authority regarding educational issues. At the same time, the superintendent is, in most cases, an employee of a politically appointed school board. While norms have traditionally encouraged superintendents to use caution with respect to political discourse (Boyd, 1974), social media has created a new platform upon which they can reach a broad range of stakeholders regarding many issues, including politics. This study seeks to better understand the emerging practice of political discourse by superintendents on Twitter. Employing discursive psychology principles (Potter & Wetherell, 1992), I will analyze the political tweets of superintendents and position current practices in relation to established role conceptualizations of the position. Findings include that superintendents utilize Twitter as a tool to establish their positions as political insiders and as advocates for students.